2018
DOI: 10.5650/jos.ess18073
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of γ-Oryzanol from Rice Bran Acid Oil by an Acid-base Extraction Method with the Assistance of Response Surface Methodology

Abstract: an inexpensive byproduct, especially using a simple, rapid and low cost process. Crude rice bran oil CRBO contains approximately 1.5-2.9 of γ-oryzanol. However, more than 90 of the initial amount of γ-oryzanol is lost and removed with the rice bran oil soapstock RBOS during the alkali refining process 8. Thus, in industrial practice, the RBOS and its acidulated form known as rice bran acid oil RBAO are excellent sources for recovery of γ-oryzanol. Several processes have been proposed for recovery of the γ-oryz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results are comparable to ours, but the resulting reaction product in their study was soap and FFAs rather than biodiesel. In another study by Sombutsuwan et al (2018), acid-catalyzed reactions were used for biodiesel production before the acid-base extraction of γ-oryzanol. The authors reported 76% recovery of γ-oryzanol (based on the amount present in the reaction product) after extraction of the aqueous phase with ethyl acetate, followed by drying under N2.…”
Section: Comparison Of Results With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are comparable to ours, but the resulting reaction product in their study was soap and FFAs rather than biodiesel. In another study by Sombutsuwan et al (2018), acid-catalyzed reactions were used for biodiesel production before the acid-base extraction of γ-oryzanol. The authors reported 76% recovery of γ-oryzanol (based on the amount present in the reaction product) after extraction of the aqueous phase with ethyl acetate, followed by drying under N2.…”
Section: Comparison Of Results With Previous Studiesmentioning
confidence: 99%
“…γ-oryzanol residing in the resulting reaction product was recovered using an acid-base extraction method, modified from Sombutsuwan et al (2018), in which NaOH was used to transform γ-oryzanol to its anionic phenoxide form (deprotonated) to make it separable from the biodiesel phase. Here, the effect of NaOH concentration on γ-oryzanol recovery was investigated to find the most suitable extraction condition as follows: the biodiesel phase (1 g) was first placed in a 50 mL Erlenmeyer flask on a magnetic stirrer and then mixed with hexane (1 mL), followed by addition of aqueous ethanolic NaOH (4 mL) which was composed of 24.09 %v/v ethanol and 75.91 %v/v of NaOH solution at a specified concentration (1, 2, 3, or 4 M).…”
Section: Extraction Of γ-Oryzanolmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, resolutions of solute compounds and the separation power of a single 100-Å Phenogel column were substantially improved when nonpolar solvent, isooctane were incorporated into the common mobile phase, toluene, and/ or tetrahydrofuran with additional a small amount of acetic acid. These were demonstrated for the separations of TG, DG, MG, FFA and wax ester in rice bran wax (Aryusuk et al, 2011), acyglycerols, FFA and OZ in rice bran acid oil (Sombutsuwan et al, 2018) and fatty acid methyl ester and steryl glucoside in biodiesel (Cheewaphan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of rice bioactive compounds such as γ-oryzanol (OZ), ferulic acids (FA), free phytosterols and triterpene alcohols (FS) received much attention due to their various applications in foods, medical and cosmetics (Verma & Srivastav, 2020). Over the last few years, many studies have focused on methods for preparation of these compounds from lowcost by-products of rice bran oil (RBO) refining (Truong et al, 2017, Sombutsuwan et al, 2018. Generally, different of these compounds required different approaches for determination.…”
Section: Introductionmentioning
confidence: 99%